2018
DOI: 10.1530/eje-17-0730
|View full text |Cite
|
Sign up to set email alerts
|

The impact of environmental temperature on the diagnosis of gestational diabetes mellitus

Abstract: GDM prevalence in Greece presents seasonal variation, with higher risk during summer due to post glucose load level variations. These variations could be attributed to differences in environmental temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 17 publications
4
37
1
Order By: Relevance
“…Although we observed a temporal trend of increasing GDM incidence as the decade progressed in this analysis we could not find a seasonal trend. This is despite seasonal trends in GDM previously have been observed in populations in Sweden 13 , Australia 14, 15 , Italy 16 and Greece 17 . However of the populations tested before where no such trend was observed 18,19 one of these was also in the U.K. 19 so our lack of seasonal trend may relate to climate or other environmental factors specific to the U.K. Alternatively, whilst at least one of the studies that found a seasonal trend used a very similar analysis technique to the one that we used 15 , other studies used analysis of variance or categorical/ordinal analyses which did not account for the recurring nature of the seasons or adjust for longer-term temporal trends 13,14,16,17 so differences from our results may relate to this.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Although we observed a temporal trend of increasing GDM incidence as the decade progressed in this analysis we could not find a seasonal trend. This is despite seasonal trends in GDM previously have been observed in populations in Sweden 13 , Australia 14, 15 , Italy 16 and Greece 17 . However of the populations tested before where no such trend was observed 18,19 one of these was also in the U.K. 19 so our lack of seasonal trend may relate to climate or other environmental factors specific to the U.K. Alternatively, whilst at least one of the studies that found a seasonal trend used a very similar analysis technique to the one that we used 15 , other studies used analysis of variance or categorical/ordinal analyses which did not account for the recurring nature of the seasons or adjust for longer-term temporal trends 13,14,16,17 so differences from our results may relate to this.…”
Section: Discussioncontrasting
confidence: 71%
“…9 Therefore another factor that could explain at least part of the increased incidence of GDM is exposure to raised or rising ambient temperatures in certain populations. [10][11][12] Following this some studies have reported seasonal variations in the incidence of GDM [13][14][15][16][17] , although this has not been observed in all populations or climates. 18,19 In this study we investigated whether there were temporal and seasonal trends in GDM incidence in our single centre population from Cambridge, U.K. which recruited pregnant women between 2001 and 2009.…”
Section: Introductionmentioning
confidence: 96%
“…In addition to risk associated with individuals, however, there may also be factors in the general environment that influence the likelihood of GDM. Several recent reports suggest that GDM incidence varies with season in diverse settings including southern Europe [7][8][9], Brazil [10], Australia [11][12][13] and Canada [14,15]. These studies show that postload glucose values and incidence of GDM increase at higher ambient temperatures [7,8,10,13,14].…”
Section: Introductionmentioning
confidence: 70%
“…The influence of seasonal variationbased on outdoor air temperatureon glucose concentrations during an oral glucose tolerance test or on the prevalence of GDM has been studied with inconsistent findings [6][7][8][9][10][11][12]. However, more recent studies have reported a seasonal variation in GDM, based on outdoor temperature [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The influence of seasonal variationbased on outdoor air temperatureon glucose concentrations during an oral glucose tolerance test or on the prevalence of GDM has been studied with inconsistent findings [6][7][8][9][10][11][12]. However, more recent studies have reported a seasonal variation in GDM, based on outdoor temperature [7][8][9][10][11][12]. The influence of seasonal variation is thought to be due to factors including alterations in blood flow, seasonal variations in food consumption and physical activity, alterations in brown adipose tissue, and vitamin D mediated effects [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%